Staggered circular nanoporous graphene converts electromagnetic waves into electricity - Lv, Hualiang; Yao, Yuxing; Li, Shucong; Wu, Guanglei; Zhao, Biao; Zhou, Xiaodi; Dupont, Robert L.; Kara, Ufuoma I.; Zhou, Yimin; Xi, Shibo; Liu, Bo; Che, Renchao; et al. (Nature communications, 2023)
Harvesting largely ignored and wasted electromagnetic (EM) energy released by electronic devices and converting it into direct current (DC) electricity is an attractive strategy not only to reduce EM pollution but also address the ever-increasing energy crisis. Here we report the synthesis of nanoparticle-templated graphene with monodisperse and staggered circular nanopores enabling an EM–heat–DC conversion pathway. We experimentally and theoretically demonstrate that this staggered nanoporous structure alters graphene’s electronic and phononic properties by synergistically manipulating its intralayer nanostructures and interlayer interactions. The staggered circular nanoporous graphene exhibits an anomalous combination of properties, which lead to an efficient absorption and conversion of EM waves into heat and in turn an output of DC electricity through the thermoelectric effect. Overall, our results advance the fundamental understanding of the structure–property relationships of ordered nanoporous graphene, providing an effective strategy to reduce EM pollution and generate electric energy. The electromagnetic (EM) energy released by electronic devices in the environment is largely wasted and contributes to EM pollution. Here, the authors report the synthesis of staggered circular nanoporous graphene enabling the absorption and conversion of EM waves into electricity via the thermoelectric effect.